Whistle him in : the story of a Maine seal - Johnson, Eleanor Noyes; Robinson, Gordon (Portland, Me. : Gannett Books, 1985)
While visiting his grandparents' saltwater farm in Maine one summer, David becomes friends with a young seal.
Keywords: Seals (Animals) -- Juvenile fiction; Friendship -- Fiction; Seals (Animals) -- Fiction; Maine -- Fiction; Maine -- Juvenile fiction